Penerapan Terapi Musik Klasik Terhadap Kecemasan Pada Pasien Gagal Ginjal Kronis Yang Menjalani Hemodialisa Di Ruang ICU RSUD Pandan Arang Boyolali - Argi Syahdila Darma; Hermawati Hermawati; Panggah Widodo (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Background: According to the World Health Organization (WHO), in 2018 the incidence of CKD worldwide reached 10% of the population, chronic kidney failure patients undergoing hemodialysis are estimated to reach 1.5 million people worldwide. Chronic kidney failure sufferers who will undergo hemodialysis often experience anxiety. One technique that can overcome the level of anxiety in patients undergoing hemodialysis is distraction technique. The distraction technique that will be given to reduce anxiety is the application of classical music, apart from being able to influence mood, now music is known to have amazing powers both physically, emotionally and spiritually. Objective: To find out the results of implementing classical music therapy for anxiety in patients with chronic kidney failure. who underwent hemodialysis in the ICU Room at Pandan Arang Boyolali Regional Hospital. Method: descriptive case study. To create a picture of classical music therapy nursing care for anxiety in Chronic Kidney Failure patients undergoing hemodialysis in the ICU room at Pandan Arang Hospital, Boyolali Regency. Results: Application of classical music therapy to 2 responses in Mr. A before therapy 4 statements of very severe anxiety after therapy 1 statement of mild symptoms, while for Mr. S before therapy 3 statements of severe anxiety and after therapy 1 statement of mild anxiety. Conclusion: there was a decrease in anxiety in both respondents after classical music therapy.